A study exploring the influences of training on teaching assistants' learning, behaviour and self efficacy - Higgins, Helen J. (2009)
There is a growing number of teaching assistants (TAs) in mainstream schools (DCFS, 2009) and research is inconclusive about their efficacy at improving outcomes for children, including those at risk of exclusion (Groom and Rose, 2005; Tennant, 2001). It has been proposed that TAs do not have enough training for their roles (Russell et al, 2005). However, there is debate about the most appropriate adult training methods (Merriam et al, 2007). Nevertheless, several writers suggest that training can influence self efficacy and this can improve performance (Giallo and Little, 2003).